2018
DOI: 10.1007/s13770-018-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells of Different Origin-Seeded Bioceramic Construct in Regeneration of Bone Defect in Rabbit

Abstract: Bone marrow derived mesenchymal stem cells (BMSC) represent an attractive cell population for tissue engineering purpose. The objective of this study was to determine whether the addition of recombinant human bone morphogenetic protein (rhBMP-2) and insulin-like growth factor (IGF-1) to a silica-coated calcium hydroxyapatite (HASi) - rabbit bone marrow derived mesenchymal stem cell (rBMSC) construct promoted bone healing in a large segmental bone defect beyond standard critical -size radial defects (15mm) in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 71 publications
0
32
0
1
Order By: Relevance
“…Previous studies reported that the pivot role, for hASCs osteogenic differentiation, is played by the HA, whereas the collagen mainly supports the survival, proliferation, and chondrogenic differentiation …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the pivot role, for hASCs osteogenic differentiation, is played by the HA, whereas the collagen mainly supports the survival, proliferation, and chondrogenic differentiation …”
Section: Discussionmentioning
confidence: 99%
“…21,22 Stem cell seeded biomaterials are now used routinely for different surgical affections. 23,24 The primary implications of these research findings remained unnoticed until recently. Commitment and differentiation are not usually thought of as reversible, but rather as multistep, unidirectional and terminal processes.…”
Section: Differentiation Studiesmentioning
confidence: 99%
“…Nau et al demonstrated that combining a vascularized periosteal flap with a β‐TCP scaffold and bone marrow‐derived mononuclear cells resulted in improved bone healing in a similar rat femur model. The use of a rabbit radial or ulnar segmental diaphyseal defect model (10, 12, 15, 20, or 30 mm long) can be another good choice . Although there is no need for internal fixation in this model, it should be noted that this type of model cannot allow the animal to apply a mechanical load through the defect.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a rabbit radial or ulnar segmental diaphyseal defect model (10,12,15,20, or 30 mm long) can be another good choice. [20][21][22][23] Although there is no need for internal fixation in this model, it should be noted that this type of model cannot allow the animal to apply a mechanical load through the defect. In addition, the adjacent ulna or radius may interfere with the results of this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation